ORGANIZATIONAL COMMITMENT: PERSON ORGANIZATION FIT AND QUALITY OF WORK LIFE - Winika Santa Rita; RA Marlien (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Human resource management (HR) is one of the key factors to get the best performance, because in addition to dealing with skills and expertise, HR management is also obliged to build conducive behavior for employees to get the best performance. In order to increase the organizational commitment of ASN (State Civil Apparatus) employees, it is necessary to analyze the factors that can support the increase in organizational commitment. The object of this research is ASN Employees. The sample used in this study is 137 respondents. The finding that partially organizational fit and quality of work life has a significant effect on job satisfaction, while person organization fit has no effect on organizational commitment. The variables of quality of work life and job satisfaction have an effect on organizational commitment. Job satisfaction as a mediation between the variable person organization fit and the quality of work life on organizational commitment Keywords: person organization fit, quality of work life, job satisfaction, organizational commitment